Crime and the media: headlines versus reality - Muraskin, Roslyn (Pearson/Prentice Hall, 2007)
Mediafication of crime : headlines v reality -- What about the media? -- The relationship of crime reporting and its effectiveness concerning the criminal justice system -- Crimes and reactions -- The Salem witchcraft trials -- The Scopes "Monkey Trial" : July 10-25 1925 -- The Menedez brothers-1989 -- Colin Ferguson-1993 -- The O.J. Simpson case-1994 -- Jon-Benet Ramsey-1996 -- Kobe Bryant-2003 -- Daniel Pelosi-2001 -- Elizabeth Ann Smart-2002 -- Scott Peterson-2002 -- Michael Jackson-2004 -- Criminal justice treatment by the media -- A star is formed : media construction of the female criminal / by Krista Gehring -- Martha Stewart : this criminal case is about lying! -- Can the mass media do good? Or no wrong? -- If a story isn't on tv or depicted by the media in America, it doesn't exist in our culture -- In conclusion